Depression, Anxiety, and Suicide After Stroke: A Narrative Review of the Best Available Evidence. Issue 4 (6th December 2021) - Chun, Ho-Yan Yvonne; Ford, Andrew; Kutlubaev, Mansur A.; Almeida, Osvaldo P.; Mead, Gillian E.
Abstract : Depression and anxiety each affect around 1 in 3 people during the first year after a stroke. Suicide causes the death of about 3 to 4/1000 stroke survivors during the first 5 years. This narrative review describes the best available evidence for the epidemiology of depression, anxiety, and suicide; their prevention; and the treatment of anxiety and depression. We conclude with directions for future research.